Legendary'sManifestation in the Poetry of Badr Shaker ASSAYAB - Hadibi, Abir; Djaghdi, Abd asalam (Milev Journal of Research and Studies, 2023)
The legend had occupied the mind of the researchers until it was made a means of expressing the positions of the contemporary human being and its national and political issues.That'swhatmade it occupy a prominent place in the field of humanities. The legend was deemed as a source of inspiration, particularly for contemporary poets. Moreover, it became the centre of their literary imagination; they employ it in their poetry to express the prevailing personal, political and social aspects. Therefore, we attempt to trace the hallmarks of monitoring the mechanisms of its function in the poetry of Badr Shaker ASSAYAB because of his pioneering use of myths in a creative artistic way. Iin addition, his ability to make it contain semantic contents related to national, patriotic and humanitarian issues.